Acute Cerebellar Strokes with Anoxic Brain Injury After a Cardiopulmonary Arrest in SARS-CoV-2 Patient - Tariq Janjua; Luis Rafael Moscote-Salazar (Acta Medica Indonesiana)
Neurological complications from novel coronavirus is becoming more common. These patients usually have primary pulmonary problem of acute lung injury. Presentation in the form of encephalitis, meningitis, Guillain-Barre syndrome and seizures are noted. It is also noted that SARS-CoV-2 has predilection for brain stem leading to patient not feeling extensive pulmonary injury. Here we share another neurological presentation.